2013
DOI: 10.1016/j.taap.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel versus diesel exposure: Enhanced pulmonary inflammation, oxidative stress, and differential morphological changes in the mouse lung

Abstract: The use of biodiesel (BD) or its blends with petroleum diesel (D) is considered to be a viable approach to reduce occupational and environmental exposures to particulate matter (PM). Due to its lower particulate mass emissions compared to D, use of BD is thought to alleviate adverse health effects. Considering BD fuel is mainly composed of unsaturated fatty acids, we hypothesize that BD exhaust particles could induce pronounced adverse outcomes, due to their ability to readily oxidize. The main objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 75 publications
7
36
0
5
Order By: Relevance
“…The concentration of A-DEP shown to significantly induce lipid droplet formation may be achievable to alveolar macrophages to induce similar effects in vivo after high concentrations of A-DEP exposure. This in theory supports the finding that DEP exposure induced accumulation of lipid droplets in alveolar macrophages in mice (Yanamala et al, 2013). Monocytes in blood can also be exposed to particles penetrated through the alveolarcapillary barrier.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The concentration of A-DEP shown to significantly induce lipid droplet formation may be achievable to alveolar macrophages to induce similar effects in vivo after high concentrations of A-DEP exposure. This in theory supports the finding that DEP exposure induced accumulation of lipid droplets in alveolar macrophages in mice (Yanamala et al, 2013). Monocytes in blood can also be exposed to particles penetrated through the alveolarcapillary barrier.…”
Section: Discussionsupporting
confidence: 87%
“…Alveolar macrophages are central in the defense against deposited PM as well as in the inflammatory pathways related to lung and cardiovascular diseases attributed to exposure to air pollution (Hiraiwa and van Eeden, 2013;Ling and van Eeden, 2009). Interestingly, a recent study showed that pharyngeal aspiration of diesel exhaust particles (DEP), the major source of UFP in urban environments, was associated with accumulation of lipid droplets in alveolar macrophages and lipid peroxidation in lung tissue (Yanamala et al, 2013). Moreover, hyperlipidemic ApoE−/− mice developed pulmonary emphysema apparently related to lipid accumulation in macrophages with subsequent cholesterol efflux and activation of the Toll-like receptor 4 signaling pathway (Goldklang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Such organic derivatives were found to exert higher toxicity than the solid PM fractions (McCormick, 2007). Recent studies reported that exposure to neat BD CE was more toxic than D, producing cardiovascular alterations as well as systemic and pulmonary inflammation in mice (Brito et al, 2010;Yanamala et al, 2013). Despite BD potential as a renewable and an economically viable fuel source, it is important to address whether and how inhalation exposure to BD CE might affect human health.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that biodiesel exhaust particles exert more toxic effects compared with mineral diesel particles. 68 Again, these results should be viewed with caution due to the exposure method employed. 69 It is obvious that there is a paucity of published data on the effects of biodiesel exhaust exposure on an intact biological system, and there is little confirmation of the evidence for altered responses from physicochemical analyses and in vitro studies.…”
Section: In Vivo Studies Using Animalsmentioning
confidence: 93%
“…66,68 The first, conducted by Brito and colleagues (2010), exposed mice for 1 h to mineral diesel exhaust, soybean biodiesel exhaust and a 50:50 blend of the two, prior to assessing a range of cardiovascular and inflammatory parameters. Compared with mice exposed to mineral diesel exhaust, mice exposed to soybean biodiesel exhaust displayed altered cardiovascular parameters, including an increase in mean corpuscular volume and increased blood leucocytes, platelets, reticulocytes and metamyelocytes.…”
Section: In Vivo Studies Using Animalsmentioning
confidence: 99%